The impact of service quality on customer satisfaction and customer loyalty: an empirical study on Islamic banks in Bahrain - Ahmed, Saad Mateen; Khaliq, Ahmad; Jan, Muhammad Tahir (2016)
The quality of service plays a vital role in any service-related economic sector, including in the banking services industry. While the service sector is a major contributor to economic activity,in-depth study on service quality and its impact on customer satisfaction have been largely overlooked. Moreover, all organizations seek quality, particularly those in the service sector, and this holds true in the banking sector. The role of service quality in the survival and success of Bahraini banks have failed to acknowledge its significant impact on the industry’s competitiveness. In service organizations, enhancing service quality is now considered as the most important step in gaining a competitive edge in the market. Bahraini Islamic banking services quality is the focus of this study. To measure Islamic banks services quality, as perceived by market followed by customer satisfaction and loyalty, eventual increased market share and increase in potential customers, enhanced productivity, increased profitability in Islamic banking business in Bahrain, are inevitable. Hence the objectives for this study would be to examine the impact of service quality on customer satisfaction and customer loyalty.The present research is expected to acknowledge achievement of customer satisfaction and customer loyalty through the measurement of service quality and to provide recommendations in developing an effective Islamic banking service quality. Therefore, any research effort undertaken to enhance the service quality of the Islamic Banks in Bahrain should be considered as an important attempt to significantly contribute and support the Islamic banking institution. This study will also provide practitioners innovative ideas for refining quality of services with the purpose of achieving a competitive advantage in the Islamic Retail Banking sector in Bahrain.